Development of dementia in patients with femoral neck fracture who experience postoperative delirium—A three‐year follow‐up study. (2nd January 2018) - Olofsson, B.; Persson, M.; Bellelli, G.; Morandi, A.; Gustafson, Y.; Stenvall, M.
Abstract : Objectives: It remains unclear to what extent postoperative delirium (POD) affects the incidence of dementia in hip fracture patients, and the methods used to detect delirium and dementia require validation. The aim of this study was to investigate the development of dementia within 3 years of femoral neck fracture repair surgery, with a focus on POD as a potential predictive factor. Methods: Patients were assessed for cognition, delirium, depression, psychological well‐being, and nutritional status during their hospitalization as well as 4, 12, and 36 months after the operation. Logistic regression models were used to analyse factors associated with POD and factors associated with the development of dementia. Results: The study sample consisted of 135 patients without a history of dementia, of whom 20 (14.8%) were delirious preoperatively and 75 (55.5%) postoperatively. Three years after their operations, 43/135 patients (31.8%) were diagnosed with dementia. A greater portion of patients diagnosed with dementia (39/43, 90.6%) than patients with no dementia (36/92, 39.1%) were included among the 75 patients who had experienced POD ( P  < 0.001). In a logistic regression model, after adjustment for covariates (age, sex, diabetes, delirium pre‐and postoperatively, hyperactive delirium, days with delirium, urinary tract infection, and Mini Nutritional Assessment score), POD emerged an independent predictor for the development of new dementia (odds ratio, 15.6; 95% confidence interval, 2.6–91.6) within 3 years after the operation. Conclusion: Geriatric hip fracture patients who exhibit POD should be monitored closely for the development of dementia.